دور رجال الطريقة التجانية في الدعوة والإصلاح والتربية الروحية الشيخ سيدي العيد بن يامة أنموذجا - الحاج أحمد, جهيدة; تجاني, نزهة (University of eloued جامعة الوادي, 2021)
تهدف هذه الدراسة إلى تحديد دور رجال الطريقة التجانية في الدعوة والإصلاح والتربية الروحية من خلال تقديم لمحة عامة حول مفهوم الطريقة التجانية وابرز زواياها وتم تقديم شخصية الشيخ سيدي العيد بن يامة رحمه الله تعالى كنموذج للإصلاح والتربية الروحية من خلال توثيق الكثير من عقود الإصلاح بين الناس، وقام بالإصلاح خارج الجزائر في تونس بالضبط، تاركا العديد من رسائل التوجيه لأبنائه يحث فيها على تعمير بيوت الله تعالى وهو نهج خلفاء الطريقة التجانية. "This study aims to define the role of the men of the Tijania Method in reform and spiritual education by providing an overview of the concept of The Tijaniya Method and its most prominent Zaouia. The personality of the great AL SHAIK Sidi Al-Eid bin Yama, may God have mercy on him, was presented as a model for reform and spiritual education through documenting many contracts of reform between people, And he did reform outside Algeria, in Tunisia exactly, He left many messages of guidance to his children urging the reconstruction of the homes of God Almighty, It is the approach of the successors of the Tijaniya method. "
دعوة واعلام
Keywords: الطريقة التجانية، الإصلاح، التربية الروحية، الشيخ سيدي العيد بن يامة.; Tijania Method, Reform , Spiritual Education, AL SHAIK SIDI Al-Eid bin Yama.